Practice and efficiency of breast self-examination among female health workers in a premier tertiary hospital in Nigeria (2017)
Background: Recommendation by physicians has been shown to motivate women to obtain one of the breast cancer screening (BCS), however information about the contribution of female health workers (FHWs) is generally lacking in the literature. The aim of this study was to ascertain BSE practice and its efficiency among female health workers. Methods: A descriptive cross-sectional study was conducted among 336 consenting FHWs at the University College Hospital (UCH), Ibadan, Nigeria, using an interviewer-administered questionnaire for data collection. Descriptive statistical tests, Chi-square test and logistic regression were used for univariate, bivariate and multivariate analyses respectively. All analysis was performed using SPSS version 21 at 5% significant level. Results: Nearly all the respondents (99.4%) were aware of breast cancer, and of BSE, CBE and mammography as breast cancer screening methods (99.1%, 97.5% and 94.6% respectively). One hundred and ninety-four (57.7%) respondents had good overall knowledge score of the disease. Health programmes appeared to be the major source of our respondents’ information on BSE. Although a larger proportion 318/336 (94.6%) practiced BSE, only 46.3% practiced it on a monthly basis. Those who resides in urban areas were 0.049 times more likely to have practiced BSE when compared with those who resides in semi-urban locations (OR = 0.049, 95% CI = 0.037 – 0.992). Conclusion: The level of awareness, knowledge and practise of BSE among the FHWs in UCH was high but the efficiency of its practice was poor among them. Continuous education of health workers by primary care providers and hospital managements on BSE screening intervention with emphasizes on competence in its practice is of utmost importance. This enables them serve as positive role models through their own participation in the behaviours being promoted.